A comparative study of students’ understanding of trigonometry in the United Kingdom and the Turkish Republic - Delice, Ali (My University, 2003)
unknown
Keywords: Geometri_Öğrenim ve Öğretim; Matematik; Öğrenim ve Öğretim_Matematik